2016
DOI: 10.1063/1.4953419
|View full text |Cite
|
Sign up to set email alerts
|

Mean flows and blob velocities in scrape-off layer (SOLT) simulations of an L-mode discharge on Alcator C-Mod

Abstract: Two-dimensional scrape-off layer turbulence (SOLT) code simulations are compared with an L-mode discharge on the Alcator C-Mod tokamak [M. Greenwald, et al., Phys. Plasmas 21, 110501 (2014)]. Density and temperature profiles for the simulations were obtained by smoothly fitting Thomson scattering and mirror Langmuir probe (MLP) data from the shot. Simulations differing in turbulence intensity were obtained by varying a dissipation parameter. Mean flow profiles and density fluctuation amplitudes are consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…The measured widths are the same (within radial resolution), 107 but the absolute radial location of the mode differs by ∼5 mm. 107,117 The absolute location determination depends on the EFIT equilibrium reconstruction to map the measurements to a common radial grid, but the difference is somewhat outside of the estimated EFIT and registration uncertainties. The reasons for the differences are thus still under investigation.…”
Section: Other Diagnostic Cross-checksmentioning
confidence: 99%
“…The measured widths are the same (within radial resolution), 107 but the absolute radial location of the mode differs by ∼5 mm. 107,117 The absolute location determination depends on the EFIT equilibrium reconstruction to map the measurements to a common radial grid, but the difference is somewhat outside of the estimated EFIT and registration uncertainties. The reasons for the differences are thus still under investigation.…”
Section: Other Diagnostic Cross-checksmentioning
confidence: 99%
“…This defies any delta-F type models based on the separation of background and fluctuating quantities. Consistent blob evolution and transport has previously mostly been studied with global fluid models and codes, such as STORM/BOUT++ (Easy et al 2014;Hoare et al 2019), GBS (Ricci et al 2012), HESEL (Nielsen et al 2016Poulsen et al 2020), TOKAM3X (Tamain et al 2016), SOLT (Russel et al 2016) or GRILLIX (Ross et al 2019), and the importance of FLR effects has been demonstrated with a delta-F gyro-fluid model (Madsen et al 2011). Recently, a full-F gyro-kinetic code (Myra et al 2020) and a full-particle particle-in-cell (PIC) code (Hasegawa & Ishiguro 2017) have been applied to the analysis of blob filament propagation, the latter also including a secondary ion species.…”
Section: Full-f Multi-species Gyro-fluid Model Of Interchange Blob Tr...mentioning
confidence: 99%
“…2016), SOLT (Russel et al. 2016) or GRILLIX (Ross et al. 2019), and the importance of FLR effects has been demonstrated with a delta-F gyro-fluid model (Madsen et al.…”
Section: Full-f Multi-species Gyro-fluid Model Of Interchange Blob Tr...mentioning
confidence: 99%
“…While the measurement regions spatially spanned by the two independent diagnostics are magnetically disconnected, we map the fluctuations to common poloidal magnetic flux coordinates based upon magnetohydrodynamic equilibrium reconstruction in the tokamak plasma using the EFIT code [52]. Deconstructing the GPI fluctuations into the turbulent n e , T e , and n 0 instead of the raw brightness from atomic emission largely resolves diagnostic misalignment challenges [53] and, in contrast with past analysis of plasma discharge 1120711021 [54], there is no radial shift applied to align the turbulent fluctuation profiles from these two independent experimental diagnostics. Profiles on these open field lines fluctuate strongly with perturbations of up to 10 -100%.…”
Section: Uncovering Dynamics In Experimental Turbulence Imaging In Al...mentioning
confidence: 99%